Islamic Consolidation in Kazakhstan: Success Story and Challenges of the Future - Ario Bimo Utomo (UIN Raden Mas Said Surakarta, 2017)
This article attempts to explain the process of Islamic consolidation in Kazakhstan, a young Muslim-majority state in Central Asia which became independent following the demise of the Soviet Union. Unlike its turbulent regional neighbors, Kazakhstan has virtually been not troubled by the threat of extremists, making its success an interesting case to discuss. There are some aspects which this essay is going to analyze. First, using the consolidation framework, I am going to examine how the rise of Islam is facilitated after the demise of the Soviet Union. Second, I also add another element namely securitization. This paper argues that securitisation is the additional strategy which creates a stable condition of Islamic consolidation in Kazakhstan. This paper concludes with giving some reflections on the future of Islam and the political stability in Kazakhstan.Â